Towards new ways of assessing the impact of local medical journals: A proposal and call for change. (October 2019) - Kanyengo, Christine Wamunyima; Monde, Mercy Wamunyima; Akakandelwa, Akakandelwa
The relevance of research output to the local community is critical to changing practice. Research relevance has to be determined using measurements that show that the knowledge that arose from that research has made an impact on society. This paper, based on a literature review and preliminary research results, advocates for research impact measurements which take account of local contexts when evaluating the relevance of a journal article or indeed any research output. It concludes that a journal should go beyond traditional measurement metrics of citation analysis and bibliometrics alone as a measure of research impact. Although it is important to standardise measurements, it is also important that local communities should be encouraged to choose measurements of research output that matter to them. The proposed ways of assessing research impact are: (a) change in policies in the health sector, (b) effect on local medical treatment guidelines, (c) effect on case management, (d) use in continuous professional development, and (e) impact on local knowledge production.